Kualitas Semen Segar Sapi Bali Umur Produktif dan Non-produktif serta Penentuan Konsentrasi Krioprotektan dalam Pengencer Tris Kuning Telur - Nabilla, Anna; Arifiantini, Raden Iis; Purwantara, Bambang (Jurnal Veteriner, 2018)
The aim of this study was to compare the quality of Bali bull fresh semen in productive group (below 10 years old) with over productive group and to evaluate the frozen semen quality of bali bull after cryopreservation in Tris egg yolk extender using Dimethyl formamide (DMF) and glycerol in three different concentrations (5%, 6%, and 7%). Semen was collected using artificial vagina. Semen then evaluated macro and microscopically. Macroscopic evaluation conducted visually and microscopic evaluation with the aid of Computer Assisted Sperm Analysis CASA. Immediatelly after evaluation, semen were divided into six aliquots and diluted with Tris egg yolk (TEY) glycerol 5% (TEYG5), TEY-glycerol 6% (TEYG6), TEY glycerol 7% (TEYG7), TEY-DMF 5% (TKTD5), TEY-DMF 6% (TEYD6) and TEY-DMF 7% (TKTD7). Results of experiment showed that there was no difference (P>0.05) among the all parameters, except for semen volume. Semen volume of productive group was higher than over productive age group. No difference was found in post thawing motility of the spermatozoa in TEY extender with 5% glycerol, and TEY with 5%, 6% and 7% DMF. The higher recovery rate of bali bull spermatozoa demonstrated by spermatozoa in TEY extender with glycerol 5% and DMF 6% (63.33±2.40 dan 68.67±2.33). It was concluded that bali bull semen quality did not differ between productive and over productive ages and post thawing semen quality of bali bull in TEY with 5-7% DMF or 5% glycerol was not also different.
Keywords: sapi Bali, kualitas semen DMF, gliserol